2016
DOI: 10.1179/2045772314y.0000000282
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurement of rectal diameter and area in neurogenic bowel with spinal cord injury

Abstract: Objective: The aim of this study was to determine the efficacy of measuring the diameter and area of the rectum using ultrasonography as an additional parameter for the evaluation of neurogenic bowel in patients with spinal cord injury (SCI). Participants: In total, 32 patients with SCI (16 patients with upper motor neuron neurogenic bowel (UMNB) and 16 patients with lower motor neuron neurogenic bowel (LMNB)) participated in this study. We divided the patients by the type of neurogenic bowel: UMNB, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The external anal sphincter is a circular muscle bundle around the internal anal sphincter, which can expand the anus at will. Studies have shown that the mean rectal diameters are 4.49±0.620.25emcm before defecation and 4.01±0.540.25emcm after defection 19 …”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The external anal sphincter is a circular muscle bundle around the internal anal sphincter, which can expand the anus at will. Studies have shown that the mean rectal diameters are 4.49±0.620.25emcm before defecation and 4.01±0.540.25emcm after defection 19 …”
Section: Design and Methodsmentioning
confidence: 99%
“…The constitutive parameters of the finite element model about the rectum in this article were determined by the existing related studies 20 . The size parameters and material parameters of the simplified rectal model are shown in Table 1 19–21 …”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the average diameter of the rectum in adults is about 20 mm 20 . Since each swing arm is composed of two short rods in equal length, the length of rod is set as l.…”
Section: Design and Strength Check Of The Proposed Aas Systemmentioning
confidence: 99%
“…Studies have shown that the average diameter of the rectum in adults is about 20 mm. 20 Since each swing arm is composed of two short rods in equal length, the length of rod is set as l. The angle between the middle ring and the upper ring is . The defecation state is shown in Figure 2.…”
Section: Check Of the Proposed Aas Systemmentioning
confidence: 99%